Transcranial Direct Current Stimulation on Parkinson's Disease: Systematic Review and Meta-Analysis - Oliveira, Paloma Cristina Alves de; Araújo, Thiago Anderson Brito de; Machado, Daniel Gomes da Silva; Rodrigues, Abner Cardoso; Bikson, Marom; Andrade, Suellen Marinho; Okano, Alexandre Hideki; Simplicio, Hougelle; Pegado, Rodrigo; Morya, Edgard (Frontiers in Neurology, 2022)
Background: Clinical impact of transcranial direct current stimulation (tDCS) alone for Parkinson's disease (PD) is still a challenge. Thus, there is a need to synthesize available results, analyze methodologically and statistically, and provide evidence to guide tDCS in PD. Objective: Investigate isolated tDCS effect in different brain areas and number of stimulated targets on PD motor symptoms. Methods: A systematic review was carried out up to February 2021, in databases: Cochrane Library, EMBASE, PubMed/MEDLINE, Scopus, and Web of science. Full text articles evaluating effect of active tDCS (anodic or cathodic) vs. sham or control on motor symptoms of PD were included. Results: Ten studies (n = 236) were included in meta-analysis and 25 studies (n = 405) in qualitative synthesis. The most frequently stimulated targets were dorsolateral prefrontal cortex and primary motor cortex. No significant effect was found among single targets on motor outcomes: Unified Parkinson's Disease Rating Scale (UPDRS) III – motor aspects (MD = −0.98%, 95% CI = −10.03 to 8.07, p = 0.83, I2 = 0%), UPDRS IV – dyskinesias (MD = −0.89%, CI 95% = −3.82 to 2.03, p = 0.55, I2 = 0%) and motor fluctuations (MD = −0.67%, CI 95% = −2.45 to 1.11, p = 0.46, I2 = 0%), timed up and go – gait (MD = 0.14%, CI 95% = −0.72 to 0.99, p = 0.75, I2 = 0%), Berg Balance Scale – balance (MD = 0.73%, CI 95% = −1.01 to 2.47, p = 0.41, I2 = 0%). There was no significant effect of single vs. multiple targets in: UPDRS III – motor aspects (MD = 2.05%, CI 95% = −1.96 to 6.06, p = 0.32, I2 = 0%) and gait (SMD = −0.05%, 95% CI = −0.28 to 0.17, p = 0.64, I2 = 0%). Simple univariate meta-regression analysis between treatment dosage and effect size revealed that number of sessions (estimate = −1.7, SE = 1.51, z-score = −1.18, p = 0.2, IC = −4.75 to 1.17) and cumulative time (estimate = −0.07, SE = 0.07, z-score = −0.99, p = 0.31, IC = −0.21 to 0.07) had no significant association. Conclusion: There was no significant tDCS alone short-term effect on motor function, balance, gait, dyskinesias or motor fluctuations in Parkinson's disease, regardless of brain area or targets stimulated.